Antibacterial Properties of Major Ethnomedicinal Plants Used by the Local People of Brahmanbaria, Bangladesh (Bangladesh Journal of Botany, 2022)
Antibiotics resistant pathogenic bacteria are one of the emerging challenges of 21st century. Recently, researchers are looking for antibacterials (therapeutic agents) from ethnomedicinal indigenous plants to be considered new sources to meet the emerging challenges. These antibacterials could be used as an alternative to conventional antibiotics against infectious human diseases. The antibacterial properties of ethnomedicinal plants used by the local people of Brahmanbaria were determined. Ethnomedicinal data was collected in between June 2015 and June 2017 from 467 local people using mainly key informant’s interviews followed by group discussions, filed interviews and plant interviews. A total of 243 ethnomedicinal plants were recorded. In order to identify the most important ethnomedicinal plants Factor of informant consensus (Fic) was calculated and 8 medicinal plants were identified based on the higher consensus of informants. These are Litseaglutinosa (Lour.), Robinson, Scopariadulcis (L.), Dalbergiasissoo (Miq.), Clerodendrumviscosum (Vent.), Holarrhena antidysenterica (L.) Wall.exDecne., Phyllanthus reticulatus (Poir.), Paederia foetida (L.) and Stephania japonica (Thunb.) Miers. Both the aqueous and ethanol extracts of leaves were screened for antibacterial activity against 8 clinical strains through disc diffusion assays. The experimental results revealed that maximum (85%) plant extracts were potentially effective in inhibiting growth of pathogenic bacteria with variable potency. Litseaglutinosa was the most effective plant species retarding microbial growth of eight tested pathogenic bacteria. This plant can be evaluated for production of potential herbal antimicrobials alternative to antibiotics.Bangladesh J. Bot. 51(4): 779-786, 2022 (December)